HUBUNGAN KOMUNIKASI ORANG TUA TERHADAP KESEPIAN EMOSIONAL PADA MAHASISWA BIMBINGAN KONSELING - Ismail, Moedtmainnah; Andi Nurhayati; Septya Suarja (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to examine the relationship between parental communication and emotional loneliness among students of the Guidance and Counseling Study Program at Universitas Muhammadiyah Palopo. Emotional loneliness is a psychological condition characterized by feelings of emptiness, alienation, and the absence of meaningful emotional closeness with significant others, including parents. Effective communication between parents and children is believed to provide emotional support that can reduce feelings of loneliness. This research employed a quantitative method with a correlational approach. The sample consisted of 108 students selected using a simple random sampling technique. Data were collected using validated and reliable questionnaires on parental communication and emotional loneliness. The data were analyzed using Pearson correlation, which showed a significant relationship between the two variables, with a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.625, indicating a strong positive correlation. These findings suggest that the better the quality of communication between students and their parents, the lower the level of emotional loneliness experienced. Therefore, open, empathetic, and supportive communication from parents is essential in maintaining the emotional well-being of university students.